Local Moho distribution in the eastern Mediterranean region from gravity inversion: eastern Mediterranean Sea - Harash, Fayez; Khalaf, Amin; Al-Ansari, Nadhir; Chen, Chao; Alrawi, Imad; Al-Khafaji, Harith; Tageldin, Mohammed (Frontiers in Earth Science, 2023)
This study investigates the variations of surface Moho inverted from Bouguer gravity data beneath the northwestern Arabian plate. The results were obtained by applying the 3DINVER program developed in a MATLAB environment using the Parker–Oldenburg method. The calculation results show that the maximum Moho depth observed in the western Arabian shield approaches more than 40 km, while the minimum values of 16–20 km are mainly concentrated beneath the Mediterranean Sea. A key innovation of this study is its implementation of exponential density contrast decrease in the sediment–basement interface in the Syrian part of the Arabian plate. The gravity anomaly of the sediment is computed using a density contrast which varies exponentially with depth, leading to a more accurate representation of the subsurface structure and offering valuable insights into the geodynamic processes and seismogenic potential of the area. To validate the inverted results from the 3DINVER program, the study compares these findings with seismic results that show good agreement with our results from the same region. This leads to a better understanding of the crustal structure and provides insights into its implications for the geodynamic and seismogenic nature of the northwestern Arabian plate—critical for assessing the potential for earthquakes and other geological hazards. The density contrast between the Earth’s crust and mantle can be related to variations in the composition, temperature, and pressure of the rocks. These factors influence the mechanical properties of the crust, ultimately affecting the tectonic processes and seismic activity in the region.